Análisis de las Exportaciones de Cacao Colombiano entre 2012 y 2023 como Producto Emergente de la Economía del País (2025)
The purpose of this study is to analyze the Colombian cocoa market during the period from 2012 to 2023, aiming to contribute to the strengthening of the cocoa industry as an emerging product. To achieve this, a documentary methodology will be employed to gather data from secondary sources derived from scientific databases, official records, and expert organizations in the field, limited to the period from 2012 to 2023, regarding various variables such as production volumes, export destinations, and economic factors that influence Colombian cocoa trade.